BC graduates where art thou? an analysis on the curriculum of the U.P Broadcast Communication Department and the career status of its graduates since 1969 - Lapis, Jennifer Marie Baja (Quezon City College of Mass Communication, University of the Philippines Diliman, 2007)
"This study aims to find out what has happened to the Broadcast Communication (BC) graduates of the University of the Philippines, Diliman since the department was established in 1969 until present. It also tried to determine how the curriculum helped these graduates in their professional careers. The department has already produced brilliant and well-known personalities in the broadcast industry. It is interesting to find out where the other graduates ended up. There have been several studies similar to this study but these studies were not as comprehensive as this research or they may have a different focus. Jesus Palma, in his book Curriculum Development System: A Handbook for School Practitioners in Basic Education, presents what is called the "Tyler Rationale". From this perspective, the school curriculum can be viewed to have three fundamental elements: the purpose which indicates the goals of the school, the means which suggest the learning experiences and resources implemented in pursuit of the purpose have been met. These three elements constitute the entirely of the curriculum. Focus interviews were therefore conducted with the graduates of the department of test his principle. One hundred forty seven (147) graduates of the Broadcast Communication department were interviewed to know the different professions they ended up with. They were asked if the curriculum is helping them in their present profession, whether their career is in the media or in non-media related careers. Insights and comments from several former and present professors and/or lecturers were also gathered to better understand the goals or objectives of the Broadcast Communication curriculum. Several of the graduates interviewed ended up working in mainstream media or in the broadcast industry - television and radio. Many of them are working in media related fields like advertising, public relations, corporate communications and the like. But there were also many graduates who ended up working in totally different fields like information technology (IT), call center industry, marketing, law, etc. According to most of these graduates, the Broadcast Communication curriculum helped them in their professional careers. For the media practitioners, the basic TV and radio productions trained them for their job. For some of those who did not end up in mainstream media, they claim that more than the knowledge and skills learned from specific subjects, the curriculum as a whole trained them on values and what they call "life skills" like discipline, time management, creativity, etc. But there were graduates working in totally different fields who declared that the curriculum was not much of use to them. These graduates nevertheless, expressed their pride of becoming UP Broadcast Communication alumni and they even gave recommendations and suggested specific subjects to further enhance the curriculum. The study concludes, based on the research framework, that the curriculum is able to contribute to the preparation of most graduates for their professions, whether in media or not. But there are outside factors such as lack of equipment and incompetent teachers that hinder the Broadcast Department to produce the "ideal graduate", a media practitioner. Based on the results of this study, future researchers are highly encouraged to pursue this research. The researchers recommend to other researchers to pursue this study further. This is to enhance the curriculum and for the department to be updated on what is happening to its graduates. Another recommendation would be for a future study to be made on more specific subjects like the effectiveness of production classes or the electives. Also, this kind of research is recommended to be concluded by other Mass Communication students - Journalism , Film and Communication Research majors, to find out the effectiveness of the different curricula in the college and therefore be able to know what kind of professionals the college produces as a whole."
Vita.
Thesis (A.B. Broadcast Communication)--University of the Philippines Diliman